Product Development and Social Media Create Purchase Decisions (A Survey on Wedding Planner Service Customers at Casturia Photography Bandung) - Zulfikar, Taufik; Fauziadewi, Ridwani (Budapest International Research and Critics University, 2022)
During a pandemic like the one we are facing today, wedding services must adjust their services to the regulations stipulated by the government and be able to communicate these service products. Product development and social media are the marketing strategies applied by Casturia photography to influence the purchase decision process of its clients. This study was aimed at studying the effect of product development and social media on purchase decisions. The research method used in this study was quantitative with multiple linear regression analysis tools. The sample of this research was 96 clients of Casturia photography. The results showed that there was a positive and significant effect of product development and social media on purchase decisions either partially or simultaneously.